ICT training for the business competitiveness of the agro-industrial sector in the city of Cucuta (2022)
Information and communication technologies (ICTs) are considered an essential tool in business strategy to promote the competitiveness of companies, with their implementation becoming more relevant in times of global crisis, such as the one currently experienced during the Covid-19 pandemic. The research objective of this paper was to design an ICT training strategy for business competitiveness in the agro-industrial sector, starting with the descriptive phase provided in this paper. This research is based on a quantitative approach and includes a detailed description of agro-industrial companies’ current difficulties in using ICTs. A survey-type instrument with closed questions was carried out. In its application, a sampling plan was made, studying 12 agro-industrial companies from the city of Cúcuta; 242 employees were analyzed. It was identified that agro-industrial companies are at a medium level, scoring 92.9% in ICT use in technology, competitiveness factor, and business education. In conclusion, these companies located at a medium level in terms of ICT use of basic software and hardware for the daily tasks that employees must perform based on the completion objectives proposed by the company. However, in the face of a crisis such as the Covid-19 pandemic, the companies must follow an emergency protocol of migrating to new virtual spaces because these become the main resource for their existence. As a scientific novelty, the research shows that despite the tensions caused by the Covid-19 pandemic, and although ICTs provided support for the survival of agro-industrial organizations, the city companies have not found ways or strategies to take advantage of the ICT benefits in communication processes, competitiveness, and strengthening of human capital.